Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices - Pradeep Natarajan (Nature Portfolio, 2021)
The influence of X chromosome genetic variation on blood lipids and coronary heart disease (CHD) is not well understood. Here, the authors analyse X chromosome sequencing data across 65,322 multi-ancestry individuals, identifying associations of the Xq23 locus with lipid changes and reduced risk of CHD and diabetes mellitus.